Tetracycline degradation by ozonation in the aqueous phase: Proposed degradation intermediates and pathway - Khan, M. Hammad; Bae, Hyokwan; Jung, Jin-Young (ELSEVIER, 2010)
During the ozonation of tetracycline (TC) in aqueous media at pHs 2.2 and 7.0, the effects of pH variations, protonation and dissociation of functional groups and variation in free radical exposure were investigated to elucidate the transformation pathway. Liquid chromatography-triple quadrupole mass spectrometry detected around 15 ozonation products, and uncovered their production and subsequent degradation patterns. During ozonation at pH 2.2, the TC degradation pathway was proposed on the basis of the structure, ozonation chemistry and mass spectrometry data of TC. Ozonation of TC at the C11a-C12 and C2-C3 double bonds, aromatic ring and amino group generated products of m/z 461, 477, 509 and 416, respectively. Further ozonation at the above mentioned sites gave products of m/z 432, 480, 448, 525 and 496. The removal of TOC reached a maximum of approximate to 40% after 2 h of ozonation, while TC was completely removed within 4-6 min at both pHs. The low TOC removal efficiency might be due to the generation of recalcitrant products and the low ozone supply for high TC concentration. zonation decreased the acute toxicity of TC faster at pH 7.0 than pH 2.2, but the maximum decrease was only about 40% at both pHs after 2 h of ozonation. In this study, attempts were made to understand the correlation between the transformation products, pathway, acute toxicity and quantity of residual organics in solution. Overall, ozonation was found to be a promising process for removing TC and the products initially generated. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: ETHYLENEDIAMINETETRAACETIC ACID EDTA; WATER; OZONE; OXIDATION; ANTIBIOTICS; PHARMACEUTICALS; CONSTANTS; KINETICS; PHENOLS